2008
DOI: 10.1177/0011000007309488
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Heterosexism

Abstract: Counseling psychologists can expect to encounter lesbian, gay, and bisexual (LGB) individuals in their lives, as students, colleagues, friends, clients, and/or family members. Most of the LGB individuals encountered by counseling psychologists have experienced the negative consequences of internalized heterosexism/internalized homophobia (IH). Yet many counseling psychologists are not adequately prepared to deal with the negative effects of IH on LGB persons' lives. This Major Contribution provides readers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(57 citation statements)
references
References 48 publications
1
55
0
1
Order By: Relevance
“…Mustanski's (2010, 2011) meta-analytic reviews on the relationship between IH and mental health and between IH and sexual risk taking found largely small effect sizes for these associations. Recently, Szymanski and collaborators (Szymanski, Kashubeck-West, & Meyer, 2008a, 2008b examined the psychometric properties of instruments for measuring IH. They concluded that there were at least five measures with adequate reliability and validity support, but that more research was needed related to the measurement of IH, particularly with regard to racial and ethnic minority LGB individuals.…”
mentioning
confidence: 99%
“…Mustanski's (2010, 2011) meta-analytic reviews on the relationship between IH and mental health and between IH and sexual risk taking found largely small effect sizes for these associations. Recently, Szymanski and collaborators (Szymanski, Kashubeck-West, & Meyer, 2008a, 2008b examined the psychometric properties of instruments for measuring IH. They concluded that there were at least five measures with adequate reliability and validity support, but that more research was needed related to the measurement of IH, particularly with regard to racial and ethnic minority LGB individuals.…”
mentioning
confidence: 99%
“…An interesting hypothesis presented by Szymanski, Kashubeck-West, and Meyer (2008), which is also a belief that is prevalent in the gay community, is that men who are overly concerned with their masculinity are struggling with internalized homophobia and may have a more developed heterosexist attitude.…”
Section: Masculinitymentioning
confidence: 99%
“…In themselves these terms are not problematic to theory; the terms were developed out of a need to refine theoretical frameworks as research literature on attitudes toward sexual orientation minorities expanded. For example, heterosexism developed out of critiques of the term homophobia, and had been defined by some authors as an explicit attitude or claim that heterosexual life styles were superior to homosexual ones and used to deny sexual orientation minority persons rights, as juxtaposed to negatively valence attitudes in general toward sexual orientation minorities (as the term homophobia might be interpreted to be; Morin and Garfinkle 1978;Szymanski et al 2008a). Thus, the intention of developing the term heterosexism was to differentiate it from homophobia in a specific way.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…For example, the literature base in areas related to homophobia/ heterosexism, etc., have been critiqued for use of measures that may not reflect the intended constructs and for using confusing and overlapping terminology (Smith et al 2012;Szymanski et al 2008b), and some of this controversy may result from fuzzy or unclear definitions of constructs. Relatedly, it is somewhat surprising that among their critiques of homophobia, McCormack and Anderson (2014) did not address the argument that homophobia is not a phobia and thus is overly and overtly pathologizing-an argument that would persist against the term homohysteria (Szymanski et al 2008a). Lapses in clarity, and consistency with prior work, contribute to definitional problems in McCormack and Anderson's work.…”
Section: Operational Definitionsmentioning
confidence: 99%